REKONSTRUKSI HUKUM PENYELESAIAN SENGKETA PASAR MODAL SYARIAH: PENGUATAN ASPEK REGULASI UNTUK MEMBERIKAN KEPASTIAN HUKUM - Edi Hudiata (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2017)
The regulation of the Islamic capital market following the rules contained in Law 8/1995 on Capital Market, DSN MUI Fatwa No. 40 / IX / 2003, Bapepam-LK Number IX.A.13, No. IX.A.14, and No. II. K.1 From that rules, nothing has clearly set the Islamic capital market dispute resolution, both litigation and non-litigation resulting in a legal vacuum (leemten in het recht). Islamic economic dispute settlement provisions, including the dispute over the Islamic capital market, is only found in Law 3/2006. Through quantitative research methods, the study sought to harmonize the empty rules at the same time filling thus legal vacuum. The research concluded that the settlement litigation of disputes in Islamic capital markets settled in the Religious Court, while in non-litigation resolved through BASYARNAS (National Sharia Arbitration Board) and / or as other civil disputes can also be resolved through Alternative Dispute Resolution in accordance with Law 30/1999.Keywords: legal vacuum, the Islamic capital market.